Utilization of Generative AI Tools in Assignment Completion Among DCS and DCV Students - Borhan, Nor Radhiah; Kimlin, Halizayanie; Ismail, Rasma Suzieyantee (Tropical Scientific Journal, 2026)
Objective: This study explores the types, frequency of use, purpose and perception of GenAI tools used in academic tasks and assessments among students from Diploma in Digital Creative Technology Arts (DCS) and Diploma in Digital Creative Technology Video Production (DCV) programmes. Research Method: The study used a quantitative research design by adapting a structured online questionnaire. The questionnaire was distributed to students, and the collected data was analysed using SPSS. Reliability testing and descriptive statistics were conducted to examine the frequency of GenAI tools usage and the mean scores for purpose and perception items. Additionally, thematic review was applied to analyse the open-ended responses. Findings: Results indicate frequent use of text-based GenAI tools, design platforms, and proofreading applications. Students mainly utilize GenAI tools for idea generation, saving time, improving content quality, and enhancing learning support. The perception towards GenAI is positive, with high agreement on ethical use and interest in attending AI-related training. These findings are also aligned with the Technology Acceptance Model (TAM), where students’ adoption of GenAI tools is influenced by its usability and user friendliness. Originality: Focusing on Malaysian polytechnic students, this study contributes to the growing body of literature concerning the usage of Generative AI (GenAI) in creative-based higher education programs. The findings provide practical insights for integrating AI literacy, ethical guidelines, and skill-based training digital creative and media-related curricula.